2022
DOI: 10.1108/aam-11-2021-0061
|View full text |Cite
|
Sign up to set email alerts
|

“We need to keep making stuff, regardless of what the situation is”: creativity and the film festival sector during COVID-19

Abstract: PurposeIn-person film festival experiences have faced uncertain futures since the spread of COVID-19. Snap-lockdowns, unclear and rapidly changing rules to public density allowances in theatres, distribution and challenges of “working-from-home” have become prominent issues to creative and cultural workers employed within the film festival ecosystem. The purpose of this paper, drawing from a series of interviews with film festival directors, organisers and workers within Australia, offers insight into the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The findings revealed that Edinburgh's Festivals responded in similar ways to other events and festivals, initially by changing venues and moving content online (Teevan, 2021). These changes enabled the festivals to engage with artists and audiences in new ways in creating content and experiences (Richards and Pacella, 2022). The findings also show how a new and comprehensive support network was established with both external support through government subsidies (Davies, 2020) and also campaigns and support from new grant-making bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that Edinburgh's Festivals responded in similar ways to other events and festivals, initially by changing venues and moving content online (Teevan, 2021). These changes enabled the festivals to engage with artists and audiences in new ways in creating content and experiences (Richards and Pacella, 2022). The findings also show how a new and comprehensive support network was established with both external support through government subsidies (Davies, 2020) and also campaigns and support from new grant-making bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Yet researchers have noted that the desire to reach out and connect with audiences despite the COVID-19 restrictions led to opportunities for creativity and new festival delivery models (Richards and Pacella, 2022). Examining the 2020 Burning Man festival, Rowen (2020) noted the role of audiences and festival organisers in co-creating content and, with the move to online delivery modes, proposed that festivals were moving beyond their geographical and temporal boundaries.…”
Section: Literature Review Innovationmentioning
confidence: 99%
“…Simultaneously, the main barrier to developing activities using computerised solutions was the lack of sufficient financial resources that cultural institutions could spend on this purpose (Raimo et al, 2021). Changing ways of functioning for entities in the cultural industry was also considered in terms of prospective creativity within the framework of professional activities (Richards & Pacella, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic restricted human mobility worldwide, and the event industry was also profoundly affected during this period (Davies, 2021; Chi et al , 2022; Richards and Pacella, 2022). Film festivals, which have an essential place in the field of event management, were also negatively affected due to uncertainty (Bachman and Hull, 2022; Hanzlíka and Mazierska, 2022; Richards and Pacella 2022). The rise in hybrid film festivals, which consist of online screenings, began in response to the uncertain nature of event management (Richards and Pacella, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Film festivals, which have an essential place in the field of event management, were also negatively affected due to uncertainty (Bachman and Hull, 2022; Hanzlíka and Mazierska, 2022; Richards and Pacella 2022). The rise in hybrid film festivals, which consist of online screenings, began in response to the uncertain nature of event management (Richards and Pacella, 2022). With the slowdown of the pandemic and the gradual lifting of restrictions, social and cultural events such as film festivals have started to be held face-to-face with mask and distance measures.…”
Section: Introductionmentioning
confidence: 99%